An observational study on global longitudinal strain in acute coronary syndrome and its correlation with coronary angiogram - Raghupathi, A.; Kannan, P.; Veeramani, C.; Sivanesan, P. (International Journal of Advances in Medicine, 2024)
Background: Coronary angiography (CA) is crucial for diagnosing acute coronary syndrome (ACS) and assessing coronary artery disease (CAD), enabling healthcare providers to determine treatment options and assess the risk of cardiovascular events. Global longitudinal strain (GLS) is a sensitive marker of cardiac function. This study aimed to determine the correlation between GLS in ACS and CA findings. Methods: This prospective observational study was conducted at the cardiology department of the Salem government medical college. The study involved transthoracic echocardiography (TTE) to assess LV volumes, ejection fraction (EF), and LVGLS and strain analysis using 2D echocardiography to measure regional longitudinal peak systolic strain in different LV segments. CA was performed to visualise the coronary vessels and detect significant CAD. Results: The study population consisted predominantly of male patients (n=93, 62%), with notable smoking (n=48, 32%) and alcohol consumption (n=36, 24%). A significant majority of the patients (n=111, 74%) exhibited ECG abnormalities. Obstruction was present in 82% of the patients (n=123), with those showing impaired myocardial function compared to those without obstruction. GLS values below 13.95 were more common in patients with obstruction (n=8 out of 11), indicating reduced myocardial deformation. The GLS demonstrated excellent diagnostic performance for detecting significant coronary artery obstruction, with a high sensitivity of 88.89%, specificity of 90.63%, and overall accuracy of 90.24%. Conclusions: Our study revealed a strong correlation between reduced GLS and CAD, highlighting its importance in CAD assessment and risk stratification in ACS. GLS demonstrated excellent diagnostic performance for detecting significant CAD, showing high sensitivity and specificity.